A horticulturally interesting new form of Cochleanthes aromatica - Pupulin, Franco (2024)
A new and horticulturally interesting form of the Costa Rican native orchid, Cochleanthes aromatica, is described and illustrated as f. carnea. The diversity in the color and pattern of orchid flowers is discussed in the light of the evolutionary interaction between their habitat and pollinating agents, which one or another metabolic pathway. Among the flower pigments anthocyanins play a key role although, being also involved in other essential biological functions of plants. The pattern of anthocyanin synthesis, their biochemistry, and the sensitivity of these polyphenolic compounds to abiotic factors are briefly summarized.